The Effect of Email Keypal Project on the Enhancement of the Writing and Reading Skills of Elementary School ELF Children in Saudi Arabia - Al-Sanad, Mashael Abdullah (Journal of Humanities & Social Sciences, 2019)
The aim of this study was to investigate the effects of an email Keypal project on the English reading and writing skills of a group of Grade 5 elementary school students studying English as a Foreign Language in Saudi Arabia. A mixed methods approach was used with a quasi-experimental procedures, interviews were used to collect data. 10 pupils studying at a girls’ school in Saudi Arabia participated in an email project with partners from a Muslim school in Canada. The Saudi pupils were pre- and post-tested on their reading and writing skills, and the t-tests on the mean scores indicate that the Keypal project helped the participating pupils improve their reading and writing skills significantly more than the pupils who did not participate over this term. The results of this study seem to indicate that Keypal projects could be a useful way of including technology in Saudi schools as they provide learners with a genuine audience for their work and could help to motivate learners and develop their language skills.
Keywords: pen pal; improvement; reading; writing; primary